CH4 conversion over Ni/HZSM-5 catalyst in the absence of oxygen: decomposition or dehydroaromatization?. Issue 32 (27th March 2020) - Xu, Yuebing; Chen, Mengyao; Liu, Bing; Jiang, Feng; Liu, Xiaohao
Abstract : Complete CH4 decomposition occurs over Ni clusters supported on HZSM-5 zeolite, while CH4 forms aromatics over Ni-exchanged sites on HZSM-5 with high selectivity, in the absence of O2 . Abstract : The different chemical states and locations of Ni species in HZSM-5 result in different directions of CH4 reaction. Supported Ni clusters caused complete CH4 decomposition, while Ni-exchanged sites anchored at Brønsted acid sites, can appropriately activate CH4 into CH x species which are important precursors to produce aromatics. This study suggests a catalyst construction strategy for selective conversion of CH4 towards value-added chemicals by placing active metal at specific sites.